DRY-PORT DEVELOPMENT TO SUPPORT DISTRIBUTION CHAINS OF EXPORT-IMPORT COMMODITIES IN INDONESIA - Johannes Anwar; Sutanto Soehodno (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2011)
This research discusses on study undertaken for improving the distribution chains of export-import commodities in indonesia. As for capacity, the existing Tanjung Priok Port has reached its crucial capacity to serve such commodities whilst surrounding land-use has already been dense with city development, it seems impossible to increase its capacity. Two possibilities stand for such capacity improvement are to develop other port at different point or to develop dry-port away but closer to industrial estate as focal point. A study for the latter, therefore, is undertaken to figure out the feasibility. Lemah Abang- Bekasi, an area of neighboring city of Jakarta, as proposed focal point is analyzed as spot of dry-port. This area is within the industrial estates whereas upstream of export-import commodity flows. This study conduct as market research comprising of three steps of following analyses, namely : analysis of existing or identified problems, formulation of export-import model for its projection and market perception on proposed dry-port development, especially related to price sensitivity, comparative and competitive advantages, as well as sound transportation. In conclusion, study has revealed, through sequences of analyses, that dry-port development at Lemah Abang has competitive and adventageous values in supporting Tanjung Priok port in export-import commodities handling.'